2003
DOI: 10.2337/diabetes.52.11.2748
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Elevated Free Fatty Acid Levels to the Lack of Glucose Effectiveness in Type 2 Diabetes

Abstract: Increased circulating free fatty acids (FFAs) inhibit both hepatic and peripheral insulin action. Because the loss of effectiveness of glucose to suppress endogenous glucose production and stimulate glucose uptake contributes importantly to fasting hyperglycemia in type 2 diabetes, we examined whether the approximate twofold elevations in FFA characteristic of poorly controlled type 2 diabetes contribute to this defect. Glucose levels were raised from 5 to 10 mmol/l while maintaining fixed hormonal conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 60 publications
7
65
1
2
Order By: Relevance
“…In addition, suppression of EGP by other stimuli, e.g., glucose, may still be unaltered. Indeed, hepatic "glucose effectiveness" may be at least as important as hepatic insulin action in the regulation of EGP (41), and correction of this defect in type 2 diabetes has been demonstrated with reduction in FFA levels (42). Furthermore, because baseline plasma glucose levels were measured at 3:00 A.M. before initiating insulin infusion, insulin levels were relatively low, and thus improved hepatic insulin action would have been less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, suppression of EGP by other stimuli, e.g., glucose, may still be unaltered. Indeed, hepatic "glucose effectiveness" may be at least as important as hepatic insulin action in the regulation of EGP (41), and correction of this defect in type 2 diabetes has been demonstrated with reduction in FFA levels (42). Furthermore, because baseline plasma glucose levels were measured at 3:00 A.M. before initiating insulin infusion, insulin levels were relatively low, and thus improved hepatic insulin action would have been less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Since being able to sense and appropriately respond to hyperglycaemia are imperative to achieving glucose homeostasis, understanding the mechanisms whereby this regulation is lost in type 2 diabetes is of great clinical importance. We and others have previously demonstrated important effects of increased NEFAs on glucose effectiveness and the upregulation of GNG in humans [7][8][9]11]. Given the striking effect of hyperglycaemia in inhibiting net glycogenolysis [23], it is of considerable importance to determine the impact of elevated NEFAs on this regulation in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…HY-NEFA (n07): 4 h hyperglycaemic (∼10 mmol/l) pancreatic clamp studies with infusion of Liposyn 20% (Abbott Laboratories, North Chicago, IL, USA) throughout the studies (0.42 ml/min) to reproduce the moderately elevated NEFA levels observed in poorly controlled type 2 diabetes [11,12]. Of note, since Liposyn raises plasma glycerol levels, we previously examined the effect of glycerol alone on EGP in healthy individuals at levels similar to those seen with Liposyn infusion [11]. There was no difference in EGP during euglycaemia and no effect on glucose effectiveness with hyperglycaemia during glycerol infusion compared with matched controls.…”
Section: Eu (N07): 4 H Euglycaemic (∼5 Mmol/l) 'Pancreaticmentioning
confidence: 99%
“…It has been demonstrated that a decrease in free fatty acids can improve glucose effectiveness in both normal participants and individuals with type 2 diabetes. 30 Indeed, glucose effectiveness, which estimates glucose disposal independent of insulin, was the only parameter by FSIVGTT that increased significantly at 1 month following liposuction. Hypothetically, this could be related to the loss of adipose tissue with liposuction signaling the need for adipogenesis, and an increase in adipogenic factors that also increase acutely the glucose effectiveness.…”
Section: Discussionmentioning
confidence: 99%